Gamma-aminobutyric acid interactions with phytohormones and its role in modulating abiotic and biotic stress in plants - Syed Nazar ul Islam; Shaista Kouser; Parveena Hassan; Mohd Asgher; Ali Asghar Shah; Nafees A. Khan (Stress Biology, 2024)
Abstract Gamma-aminobutyric acid (GABA), a ubiquitous non-protein 4-carbon amino acid present in both prokaryotic and eukaryotic organisms. It is conventionally recognized as a neurotransmitter in mammals and plays a crucial role in plants. The context of this review centers on the impact of GABA in mitigating abiotic stresses induced by climate change, such as drought, salinity, heat, and heavy metal exposure. Beyond its neurotransmitter role, GABA emerges as a key player in diverse metabolic processes, safeguarding plants against multifaceted abiotic as well as biotic challenges. This comprehensive exploration delves into the GABA biosynthetic pathway, its transport mechanisms, and its intricate interplay with various abiotic stresses. The discussion extends to the nuanced relationship between GABA and phytohormones during abiotic stress acclimation, offering insights into the strategic development of mitigation strategies against these stresses. The delineation of GABA's crosstalk with phytohormones underscores its pivotal role in formulating crucial strategies for abiotic stress alleviation in plants.